Pengaruh Profitabilitas dan Solvabilitas terhadap Tax Avoidance pada Perusahaan Produksi Barang Konsumsi (Consumer Goods) yang Terdaftar di Bursa Efek Indonesia Periode 2022-2024 - Rendy Azhar; Daryanto Daryanto (AKUNTANSI 45, 2026)
This study aims to examine the effect of profitability and solvency on tax avoidance in consumer goods manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The research uses a quantitative approach with multiple linear regression analysis. The population consists of consumer goods manufacturing companies listed on the Indonesia Stock Exchange, with 17 companies selected as samples through purposive sampling. Profitability is measured using Return on Assets (ROA), solvency is proxied by the Debt to Equity Ratio (DER), and tax avoidance is measured using the Cash Effective Tax Rate (CETR). The results show that profitability has a significant negative effect on tax avoidance, indicating that companies with higher profitability tend to engage less in tax avoidance practices. Meanwhile, solvency has a significant positive effect on tax avoidance, suggesting that companies with higher debt levels are more likely to implement tax avoidance strategies. Simultaneously, profitability and solvency significantly influence tax avoidance, with the model explaining 38.2% of the variation in tax avoidance practices.